2018
DOI: 10.4103/ijccm.ijccm_395_16
|View full text |Cite
|
Sign up to set email alerts
|

Serum Estradiol Level at Intensive Care Unit Admission and Mortality in Critically Ill Patients

Abstract: Context:It has been observed that sex hormones may play a role in inflammatory processes and mortality of critically ill patients.Aims:The aim was evaluated the relationship between serum estradiol level at Intensive Care Unit (ICU) admission and mortality of critically ill patients.Settings and Design:This study was a prospective cohort conducted in one mixed ICU.Subjects and Methods:In heterogeneous group of critically ill patients admitted to the ICU, we measured serum estradiol at admission time.Statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This hormone is inhibited by class I cytokines and TNF alpha during stress. However, its peripheral production by enzyme aromatase in adipose tissue is activated regardless of gender [ 73 ]. Estradiol levels were measured in critically ill patients before management in intensive care units (ICUs), and the differences were remarkable between survivors and non-survivors ( p < 0.01) in whom the mean levels of estradiol were 62.2 versus 116 pg/mL, respectively [ 73 ].…”
Section: Clinical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…This hormone is inhibited by class I cytokines and TNF alpha during stress. However, its peripheral production by enzyme aromatase in adipose tissue is activated regardless of gender [ 73 ]. Estradiol levels were measured in critically ill patients before management in intensive care units (ICUs), and the differences were remarkable between survivors and non-survivors ( p < 0.01) in whom the mean levels of estradiol were 62.2 versus 116 pg/mL, respectively [ 73 ].…”
Section: Clinical Backgroundmentioning
confidence: 99%
“…However, its peripheral production by enzyme aromatase in adipose tissue is activated regardless of gender [ 73 ]. Estradiol levels were measured in critically ill patients before management in intensive care units (ICUs), and the differences were remarkable between survivors and non-survivors ( p < 0.01) in whom the mean levels of estradiol were 62.2 versus 116 pg/mL, respectively [ 73 ]. Another study from 2011 reported that high estradiol levels for ICU admission were associated with high mortality in a cohort of 1408 critically ill patients (14.1%, 95% CI 12.3–16).…”
Section: Clinical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“… 54 The increased risk of death with serum estradiol elevations is seen with other forms of acute injuries in both men and women. 55 , 56 Whether this is due to a direct effect of estradiol in exacerbating or ameliorating injury or it just a biomarker with no direct role in injury remains to be studied. Estrogens, but not anabolic androgen steroids, are associated with both an increased serum triglyceride levels and pancreatitis, 57 but the source of these steroid hormones remains to be determined.…”
Section: Acute Pancreatitismentioning
confidence: 99%